Pengaruh dana alokasi umum dan investasi sektoral terhadap belanja modal pemerintah di Provinsi Aceh - Jemeli, Jemeli; Ulfa, Maulidza; Haniya, Faiza Afin; Akbar, Atala; Zulkarnain, Teuku (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This research analyzes the influence of the General Allocation Fund (DAU) and sectoral investment on government capital expenditure in Aceh Province, with a focus on the downstrea ming of natural resources (SDA). The method used is multiple linear regression with secondary data from regional government financial reports and the Central Statistics Agency for the period 2015-2022. The research results show that DAU has a positive and significant effect on capital expenditure, especially for the infrastructure budget that supports natural resource downstreaming. Sectoral investment also plays an important role in increasing government capital capacity and developing the natural resource processing industry, which creates jobs and strengthens the local economy. In conclusion, DAU and sectoral investment have a strategic role in encouraging natural resource downstreaming. The government is advised to optimize the use of DAU and encourage sectoral investment to support infrastructure development. Further research is needed to explore other factors and the long-term impact of capital expenditure on regional economic growth